PENGARUH REBUSAN KAYU MANIS (Cinnamomum Burmanii) TERHADAP KADAR GULA DARAH PUASA PENDERITA DIABETES MELLITUS TIPE 2 - R. Meida Wanti; Yesi Hasneli; Hellena Deli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2019)
Cinnamon (Cinnamomum Burmanii) is one of the herbs that contains an activesubstance polyphenol that works by increasing insulin receptors in cells. This study uses 10 grams of cinnamon boiled with 100 ml of water. The purpose of this study was to determine the effect of cinnamon decoction on fasting blood sugar levels in type 2 diabetes mellitus patients with a research design Quasy Experiment. The study sample was 34 respondents taken by purposive sampling technique which was divided into 2 groups: 17 experimental group respondents who were given cinnamon stew twice a day for 3 consecutive days and 17 control group respondents who were not given cinnamon stew. Both groups continued to take the medication given by the doctor. The measuring instrument used was the observation sheet and glucometer by measuring blood sugar pre test on the first day andblood sugar post test for 3 consecutive days after consuming cinnamon stew. The analysis used is univariate analysis to describe the characteristics of each respondent and bivariate analysis using the Dependent Sample t Test in the experimental group and the test Wilcoxon in the control group. Homogeneity test results showed no differences in the characteristics of subjects from the two groups. There were significant differences in the mean blood sugar levels of the pre test and post test in the experimental group with p value 0.034, whereas in the control group no differences were found with p value 0.463. The conclusion is the effect of cinnamon stew on decreasing fasting blood sugar levels of type 2 diabetes mellitus patients in the working area of Harapan Raya Pekanbaru Health Center.Keywords: cinnamon (cinnamomum burmanii), diabetes mellitus, fasting blood sugar.